Pengaruh Motivasi dan Kompensasi terhadap Kinerja Karyawan di Paul Bakery Pondok Indah Mall 3 - Sekar Ayu Niken Indra Patria (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Motivation and compensation are very important, because compensation is the main encouragement or motivation for an employee to work. This means that employees use knowledge, skills, energy and time not merely to dedicate or devote themselves to the company, but for another purpose, namely expecting rewards or remuneration for the results they have provided. Therefore, determining compensation related to work performance or productivity is very important. So that apart from realizing employee efficiency and effectiveness, it can also be demonstrated for the continuity of organizational activities and company plans (programs) in the future. In this case, the various types of human needs discussed will be transformed by employees into certain "wants" within the company. It is known that the definition of human needs is a very complicated matter, as well as the desires of employees towards the company, including, based on wages (salary) which is one means of satisfying physiological and egoistic needs, then job security (security of job) due to threats from technological change. This desire can really give priority to employees in feeling safe and secure in doing their work.